Online distance mathematics education in Brazil: Research, practice and policy - Maltempi, Marcus Vinicius [UNESP]; Malheiros, Ana Paula dos Santos (Springer Nature, 2010)
In this article, we address online distance mathematics education research and practice in Brazil, which are relative newcomers to the educational scene. We present the national context of education in Brazil, highlighting the organization of the educational system, and also a summary of national legislation on distance education and an overview of digital inclusion in the country. We outline the potential and relevance of distance education for the Brazilian educational system and show how it could intervene in the system. With respect to research and practice in online mathematics education, we present support for research, examples of studies and highlight different aspects being addressed, including its essential components. In addition, we discuss the synergy between distance education and teacher education, and mathematics distance education and modeling, as well as other initiatives in the national scenario. © FIZ Karlsruhe 2009.
Keywords: Distance education; Internet; Mathematics education; Modeling; Teacher education